Hollow Metal–Organic Framework/MXene/Nanocellulose Composite Films for Giga/Terahertz Electromagnetic Shielding and Photothermal Conversion - Mai, Tian; Chen, Lei; Wang, Pei‑Lin; Liu, Qi; Ma, Ming‑Guo (Nano-Micro Letters, 2024)
With the continuous advancement of communication technology, the escalating demand for electromagnetic shielding interference (EMI) materials with multifunctional and wideband EMI performance has become urgent. Controlling the electrical and magnetic components and designing the EMI material structure have attracted extensive interest, but remain a huge challenge. Herein, we reported the alternating electromagnetic structure composite films composed of hollow metal–organic frameworks/layered MXene/nanocellulose (HMN) by alternating vacuum-assisted filtration process. The HMN composite films exhibit excellent EMI shielding effectiveness performance in the GHz frequency (66.8 dB at Ka-band) and THz frequency (114.6 dB at 0.1–4.0 THz). Besides, the HMN composite films also exhibit a high reflection loss of 39.7 dB at 0.7 THz with an effective absorption bandwidth up to 2.1 THz. Moreover, HMN composite films show remarkable photothermal conversion performance, which can reach 104.6 °C under 2.0 Sun and 235.4 °C under 0.8 W cm−2, respectively. The unique micro- and macro-structural design structures will absorb more incident electromagnetic waves via interfacial polarization/multiple scattering and produce more heat energy via the local surface plasmon resonance effect. These features make the HMN composite film a promising candidate for advanced EMI devices for future 6G communication and the protection of electronic equipment in cold environments. Highlights: 1 The composite films are composed of hollow metal–organic frameworks/layered MXene/nanocellulose with unique alternating electromagnetic structures. 2 The optimized composite films exhibit excellent EMI shielding performance of 66.8 dB at GHz frequency and 114.6 dB at THz frequency. 3 The EMI shielding ability of composite films to electromagnetic waves is verified by practical visualized application simulation. 4 The composite films show remarkable photothermal conversion performance, which can reach 235.4 °C under 0.8 W cm−2.